Peran Fanatisme sebagai Variabel Moderasi terhadap Penerimaan Produk Kosmetik dan Makanan Korea Selatan oleh Konsumen Indonesia - Ummi Nadroh (Penerbit Jurnal Indonesia, 2025)
Demand and desire for a product are closely linked to cultural backgrounds and the tendencies or fanaticism of Indonesian consumers. The widespread exposure to Korean popular culture has influenced lifestyles, particularly among Indonesians with strong interests in Korean entertainment, including dramas, music, reality shows, and celebrities. This study aims to analyze the influence of cultural and marketing perspectives on the acceptance of Korean products in Indonesia specifically, as well as the moderating role of fanaticism. The adoption of products based on cultural and marketing perspectives is highly interrelated and mutually reinforcing. The study primarily focuses on Korean food and cosmetic products within the context of Muslim Indonesian consumers, who hold distinctive religious and cultural values. A mixed-method approach was used, involving focus group discussions (FGDs) and a survey of 202 Muslim respondents from Jakarta, Bandung, and Surabaya. The FGD results reveal that Korean culture holds a positive country image, and exposure to Korean entertainment fosters consumer interest in Korean products. These consumers often seek product information via social media and purchase through e-commerce and personal shopping services (jastip). Quantitative data analyzed using Structural Equation Modeling (SEM) with AMOS 22.0 show that both cultural and marketing perspectives significantly influence the acceptance of Korean products. Fanaticism, in both religious and celebrity contexts, was found to moderate these relationships. The study concludes that Korean product marketing strategies in Indonesia must consider cultural sensitivity and religious values among Muslim consumers while leveraging celebrity figures and digital platforms to enhance emotional engagement.